2022
DOI: 10.1167/tvst.11.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence and Deep Learning for Choroid Segmentation in Myopia

Abstract: Purpose To investigate the correlation between choroidal thickness and myopia progression using a deep learning method. Methods Two data sets, data set A and data set B, comprising of 123 optical coherence tomography (OCT) volumes, were collected to establish the model and verify its clinical utility. The proposed mask region-based convolutional neural network (R-CNN) model, trained with the pretrained weights from the Common Objects in Context database as well as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…There has been a focus on imaging and segmenting (particularly using machine learning) choroidal thickness using A-scan (traditionally termed biometers ) 133 and B-scan (termed o ptical c oherence t omography ) 131 , 134 , 135 based techniques to better understand the mechanism(s) of myopia control and also as a potential predictor of long-term efficacy of treatments (see IMI 2023 white paper on choroid). 132 A model using principally baseline pupil area, 1-month change of the zone 3-mm (flat) and zone 5-mm (flat/steep) keratometry was able to predict between 54% and 63% of the variation in 1-year AL elongation with ortho-k. 136 In addition, models have been developed to predict cycloplegic refractive error from demographics, noncycloplegic SER, AL/corneal curvature radius ratio, uncorrected VA, and intraocular pressure, with the results explaining 92% to 93% of the variability in Chinese school children (aged 5–18 years) 137 , 138 and 96% in children in Japan (aged 2–9 years).…”
Section: Imi Digest—clinical Myopia Control Trials and Instrumentationmentioning
confidence: 99%
“…There has been a focus on imaging and segmenting (particularly using machine learning) choroidal thickness using A-scan (traditionally termed biometers ) 133 and B-scan (termed o ptical c oherence t omography ) 131 , 134 , 135 based techniques to better understand the mechanism(s) of myopia control and also as a potential predictor of long-term efficacy of treatments (see IMI 2023 white paper on choroid). 132 A model using principally baseline pupil area, 1-month change of the zone 3-mm (flat) and zone 5-mm (flat/steep) keratometry was able to predict between 54% and 63% of the variation in 1-year AL elongation with ortho-k. 136 In addition, models have been developed to predict cycloplegic refractive error from demographics, noncycloplegic SER, AL/corneal curvature radius ratio, uncorrected VA, and intraocular pressure, with the results explaining 92% to 93% of the variability in Chinese school children (aged 5–18 years) 137 , 138 and 96% in children in Japan (aged 2–9 years).…”
Section: Imi Digest—clinical Myopia Control Trials and Instrumentationmentioning
confidence: 99%
“…They found that the retina of patients with PD became thinner, while choroidal thickness might increase. Similar to our work, Chen et al (2022) segmented the choroidal layer of highly myopic patients and non highly myopic people and compared the thickness, while they lacked the analysis of three-dimensional features, and the segmentation performance needs to be improved.…”
Section: Related Workmentioning
confidence: 85%
“…Compared to its precursor, U-Net, 56 MedT-Net had fewer errors when segmenting choroidal boundaries and provided a larger dice coefficient ( Table 1 ). Although previous models for choroidal segmentation have reported satisfactory results, 20 , 31 , 33 , 34 , 36 these were limited to choroidal segmentation alone, without consideration of the location and width of the examined choroidal area. Defining a ROI is essential for comparison across different studies and tracking longitudinal choroidal structure changes.…”
Section: Discussionmentioning
confidence: 99%